Maduramicin triggers methuosis-like cell death in primary chicken myocardial cells. (15th October 2020) - Gao, Xiuge; Ruan, Xiangchun; Ji, Hui; Peng, Lin; Qiu, Yawei; Yang, Dan; Song, Xinhao; Ji, Chunlei; Guo, Dawei; Jiang, Shanxiang
Highlights: Excessive cytoplasm vacuolations and cell death induced by maduramicin. Distinct from apoptosis and autophagy: cytoplasmic vacuolization-related cell death. Vacuolar-H+-ATPase is necessary for maduramicin-induced cytoplasmic vacuolization and cell death. Maduramicin induces methuosis-like cell death in primary chicken myocardial cells. Abstract: Maduramicin frequently induces severe cardiotoxicity in broiler chickens as well as in humans who consume maduramicin accidentally. Apoptosis and non-apoptotic cell death occur concurrently in the process of maduramicin-induced cardiotoxicity; however, the underlying mechanism of non-apoptotic cell death is largely unknown. Here, we report the relationship between maduramicin-caused cytoplasmic vacuolization and methuosis-like cell death as well as the underlying mechanism in primary chicken myocardial cells. Maduramicin induced a significant increase of cytoplasmic vacuoles with a degree of cell specificity in primary chicken embryo fibroblasts and chicken hepatoma cells (LMH), along with a decrease of ATP and an increase of LDH. The accumulated vacuoles were partly derived from cellular endocytosis rather than the swelling of endoplasm reticulum, lysosomes, and mitochondria. Moreover, the broad-spectrum caspase inhibitor carbobenzoxy-Val-Ala-Asp-fluoromethylketone (z-VAD-fmk) did not prevent maduramicin-induced cytoplasmic vacuolization. DNA ladder and cleavage of PARP were not observed in chicken myocardial cells during maduramicin exposure. Pretreatment with 3-methyladenine (3-MA) and cholorquine (CQ) of chicken myocardial cells did not attenuate cytoplasmic vacuolization and cytotoxicity, although LC3 and p62 were activated. Bafilomycin A1 almost completely prevented the generation of cytoplasmic vacuoles and significantly attenuated cytotoxicity induced by maduramicin, along with downregulation of K-Ras and upregulation of Rac1. Taken together, "methuosis" due to excessive cytoplasmic vacuolization mediates the cardiotoxicity of maduramicin. This provides new insights for understanding a nonclassical form of cell death in the field of drug-induced cytotoxicity.